Hardy-Sobolev Spaces Associated with Twisted Convolution - Jizheng Huang; Weiwei Li; Yaqiong Wang (Journal of Function Spaces)
We first define the Hardy-Sobolev spaces associated with twisted convolution; then we give the atomic decomposition. As an application, we consider the endpoint version of the div-curl theorem for the twisted convolution.